Inverted sugar syrup attained from sucrose hydrolysis using a membrane reactor (Brazilian Journal of Pharmaceutical Sciences, 2010)
Invertase, whether adsorbed on styrene-divinylbenzene copolymers or otherwise, was used for continuous sucrose hydrolysis using a cell-type membrane reactor (CTMR), coupled with an ultra (UF-100kDa), or a microfiltration (MF- pore diameter of 5 µm) membrane. In all tests, the pH (5.5), temperature (30 ºC), reaction volume (10 mL) and agitation (100 rpm) were set constant; whereas, variable parameters were: feeding rate (0.4, 0.8 and 1.6 h-1), inlet sucrose concentration (2.5, 6.5, 50 and 100 mM) and enzyme/resin ratio (1.64 mg or 3.28 mg of protein per 25, 50 or 100 mg of resin). The best result (yield of 100%, steady-state duration over 20h and specific reaction rate over 243 x 10-3 mmol/h.mE) was obtained when insoluble invertase (1.64 mg protein/100 mg resin) was used to convert 50 mM or 100 mM of sucrose solution at 0.4 h-1 using a UF-CTMR.